2017
DOI: 10.1159/000458428
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Reduces Podocyte Adhesion via Downregulation of α3β1 Integrin

Abstract: Background/Aims: Hepatitis B virus (HBV)-associated glomerulonephritis (HBV-GN) is characterized by a reduced number of podocytes due to apoptosis and shedding from the basement membrane. However, the pathological mechanism of HBV-GN is unclear. We previously showed that hepatitis B virus X protein (HBx) promotes apoptosis in tubular epithelial cells. In this study, we transfected podocytes with HBx and examined the effects on adhesion and apoptosis of these cells. Methods: Podocytes were transfected with pc-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…HBx is considered the most important determinant in viral pathogenesis (22,23); it is a necessary transcription factor for HBV replication, having an trans-activation effect, which can promote viral replication and induce apoptosis directly, and subsequently induce the occurrence of an inflammatory reaction and serve an important role in cell transformation and proliferation (24,25). Due to the widely trans-activation properties of the HBx gene and its effect on glomerular foot cells, mesangial cells and renal tubule epithelial cells (26)(27)(28)(29), it is considered to have an important role in the pathogenesis of HBV-GN (28,29). A previous study by Zhang et al (15) demon-15) demon-) demonstrated that podocyte number was significantly decreased in the glomeruli of children with HBV-GN, while HBx protein was visualized within the glomerulus in 71% children with HBV-GN, where the expression of HBx protein was localized mainly in the cytoplasm of podocytes, with lower expression in the nuclei of the podocytes (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBx is considered the most important determinant in viral pathogenesis (22,23); it is a necessary transcription factor for HBV replication, having an trans-activation effect, which can promote viral replication and induce apoptosis directly, and subsequently induce the occurrence of an inflammatory reaction and serve an important role in cell transformation and proliferation (24,25). Due to the widely trans-activation properties of the HBx gene and its effect on glomerular foot cells, mesangial cells and renal tubule epithelial cells (26)(27)(28)(29), it is considered to have an important role in the pathogenesis of HBV-GN (28,29). A previous study by Zhang et al (15) demon-15) demon-) demonstrated that podocyte number was significantly decreased in the glomeruli of children with HBV-GN, while HBx protein was visualized within the glomerulus in 71% children with HBV-GN, where the expression of HBx protein was localized mainly in the cytoplasm of podocytes, with lower expression in the nuclei of the podocytes (19).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a major method involved in podocyte decline (35,36), and the present study confirmed that HBx could increase the apoptosis of podocytes. Recently, studies have investigated the mechanisms underlying HBx-induced apoptosis of renal tubular cells (29,37), and He et al (28) suggested that HBx could reduce podocyte adhesion via downregulation of α3β1 integrin.…”
Section: Hbx Expression At Different Time Points H -mentioning
confidence: 99%
“…Podocytes or glomerular epithelial cells constitute a critical component of the glomerular filtration barrier (GFB). As podocytes have no capacity to regenerate themselves, their loss, when significant, will subsequently result in an alteration of the GBF, leading to proteinuria and renal failure [ 63 , 64 , 65 , 66 ].…”
Section: Autophagy and Kidneysmentioning
confidence: 99%
“…Podocytes or glomerular epithelial cells are terminally specialized cells that play a critical role in forming the glomerular filtration barrier. Structural changes or injuries in podocytes are associated with renal injury resulting in proteinuria and severe renal insufficiency [3][4][5][6], and contributes to DN [7].…”
Section: Introductionmentioning
confidence: 99%